Global trends in typhoid and paratyphoid, and invasive non-typhoidal salmonella, and the burden of antimicrobial resistance: a trend analysis study from 1990 to 2021 - Ke Shi; Tongdeng You (Frontiers in Medicine)
ObjectivesTo assess the global burden of typhoid and paratyphoid fever, and Invasive Non-typhoidal Salmonella (iNTS) from 1990 to 2021, and explore the burden of antimicrobial resistance (AMR) in Salmonella.MethodsData were sourced from the Global Burden of Disease Study (GBD) 2021, focusing on age–standardized incidence rate (ASIR), mortality rate (ASMR), disability–adjusted life years rate (ASDR), and annualized percent change (EAPC).ResultsFrom 1990 to 2021, the global burden of typhoid and paratyphoid fever decreased (EAPC = −4.15; 95% CI: −4.45 to −3.85). In contrast, the burden of iNTS showed a slow increasing trend (EAPC = 0.45; 95% CI: −0.32 to 1.22). The major epidemic trends were concentrated in regions with low and middle Socio–demographic Index (SDI). In high SDI regions, the age group most affected by deaths was 75 years and older, whereas in low SDI regions, particularly for typhoid and paratyphoid fever, deaths were more prevalent among children aged 0–14 years. Disability–adjusted life years (DALYs) and deaths due to multidrug–resistant Salmonella have decreased annually.ConclusionWhile the global burden of typhoid and paratyphoid fever has declined, the burden of iNTS continues to rise slowly. The growing antimicrobial resistance of Salmonella further exacerbates the global disease burden.